Notes on the jumping spider Corythalia conferta (Araneae: Salticidae), a possible myrmecophagous specialist in Argentina - Baigorria, Julián Emanuel Martín (2021)
We present data from a new study of Corythalia conferta Bayer, Höfer & Metzner, a recently described species that inhabits southern South America. A distribution update, morphological illustrations, and phylogeny of related Corythalia C. L. Koch species are presented. Also, we present data that suggest that this species may be the first Corythalia known to specialize in hunting ants (Formicidae). We describe its hunting behavior and habitat. During a 300 hour field study, we recorded 86 prey items, 98.8% of which were ants of 11 different species.